Innate Lymphoid Cells and T Cells Contribute to the Interleukin‐17A Signature Detected in the Synovial Fluid of Patients With Juvenile Idiopathic Arthritis - Rosser, Elizabeth C. (Arthritis Rheumatol, 2019)
OBJECTIVE: Evidence suggests that aberrant function of innate lymphoid cells (ILCs), whose functional and transcriptional profiles overlap with those of Th cell subsets, contributes to immune‐mediated pathologies. To date, analysis of juvenile idiopathic arthritis (JIA) immune pathology has concentrated on the contribution of CD4+ T cells; we have previously identified an expansion of Th17 cells within the synovial fluid (SF) of JIA patients. We undertook this study to extend this analysis to further investigate the role of ILCs and other interleukin‐17 (IL‐17)–producing T cell subsets in JIA. METHODS: ILCs and CD3+ T cell subsets were defined in peripheral blood mononuclear cells (PBMCs) from healthy adults, healthy children, and JIA patients and in SF mononuclear cells (SFMCs) from JIA patients using flow cytometry. Defined subsets in SFMCs were correlated with clinical measures including physician's global assessment of disease activity on a visual analog scale, number of joints with active disease, and erythrocyte sedimentation rate. Transcription factor and cytokine profiles of sorted ILCs were assessed by quantitative reverse transcriptase–polymerase chain reaction. RESULTS: Group 1 ILCs (ILC1s), NKp44− group 3 ILCs (natural cytotoxicity receptor–negative [NCR−] ILC3s), and NKp44+ ILC3s (NCR+ ILC3s) were enriched in JIA SFMCs compared to PBMCs, which corresponded to an increase in transcripts for TBX21, IFNG, and IL17A. Of the ILC subsets, the frequency of NCR− ILC3s in JIA SFMCs displayed the strongest positive association with clinical measures, which was mirrored by an expansion in IL‐17A+CD4+, IL‐17A+CD8+, and IL‐17A+ γδ T cells. CONCLUSION: We demonstrate that the strength of the IL‐17A signature in JIA SFMCs is determined by multiple lymphoid cell types, including NCR− ILC3s and IL‐17A+CD4+, IL‐17A+CD8+, and IL‐17A+ γδ T cells. These observations may have important implications for the development of stratified therapeutics.